The Readiness of Accounting Departments Management and Implementation of the Industrial Revolution Curriculum 4.0 - Sigit Hermawan; Niko Fediyanto; Wiwit Hariyanto (International Journal of Social Science and Business, 2023)
The Industrial Revolution 4.0 brings a threat to accounting graduates because many fields of accounting work can be replaced by information technology. For this reason, the accounting department in higher education must be ready with the industrial revolution 4.0 curriculum. This study aims to analyze readiness of managers of accounting study programs and the implementation of the industrial revolution 4.0 curriculum. The research is categorized as interpretive qualitative. Data were collected using in-depth interviews, focus group discussions (FGD), and documentation. The key informants in this research are the manager of the accounting study program and a team of experts from the Indonesian Institute of Accountants. The results of the study stated that the accounting department had prepared various steps to implement the industrial revolution 4.0 curriculum. The readiness of the accounting department manager and the implementation of curriculum 4.0 is carried out in several stages, namely adjusting the graduate profile, redesigning the curriculum, changing learning methods, improving the quality of human resources, improving laboratory infrastructure, and establishing partnerships with stakeholders. This study also recommends courses that are relevant and in accordance with the industrial revolution 4.0. The implication of this research is that the accounting study program has guidelines for implementing the industrial revolution 4.0 curriculum.